Real-world fuel economy and CO2 emissions of plug-in hybrid electric vehicles - Patrick Plötz; Simon Funke; Patrick Jochem (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2015)
Plug-in hybrid electric vehicles (PHEV) combine electric propulsion with an internal combustion engine. Their potential to reduce transport related green-house gas emissions highly depends on their actual usage and electricity provision. Various studies underline their environmental and economic advantages, but are based on standardised driving cycles, simulations or small PHEV fleets. Here, we analyse real-world fuel economy of PHEV and the factors influencing it based on about 2,000 actual PHEV that have been observed over more than a year in the U.S. and Germany. We find that real-world fuel economy of PHEV differ widely among users. The main factors explaining this variation are the annual mileage, the regularity of daily driving, and the likelihood of long-distance trips. Current test cycle fuel economy ratings neglect these factors. Despite the broad range of PHEV fuel economies, the test cycle fuel economy ratings can be close to empiric PHEV fleet averages if the average annual mileage is about 17,000 km. For the largest group of PHEV in our data, the Chevrolet Volt, we find the average fuel economy to be 1.45 litres/100 km at an average electric driving share of 78%. The resulting real-world tank-to-wheel CO2 emissions of these PHEV are 42 gCO2/km and the annual CO2 savings in the U.S. amount to about 50 Mt. In conclusion, the variance of empirical PHEV fuel economy is considerably higher than of conventional vehicles. This should be taken into account by future test cycles and high electric driving shares should be incentivised.
urn:nbn:de:0011-n-3278281
Keywords: 330; electric vehicles; plug-in hybrid electric vehicles; real-world fuel economy; utility factor